Comparative transcriptome profiling reveals differential defense responses among Alternaria brassicicola resistant Sinapis alba and susceptible Brassica rapa - Ahmed, Reshma; Dey, Kuntal Kumar; Senthil-Kumar, Muthappa; Modi, Mahendra Kumar; Sarmah, Bidyut Kumar; Bhorali, Priyadarshini (Frontiers in Plant Science, 2024)
Alternaria blight is a devastating disease that causes significant crop losses in oilseed Brassicas every year. Adoption of conventional breeding to generate disease-resistant varieties has so far been unsuccessful due to a lack of suitable resistant source germplasms of cultivated Brassica spp. A thorough understanding of the molecular basis of resistance, as well as the identification of defense-related genes involved in resistance responses in closely related wild germplasms, would substantially aid in disease management. In the current study, a comparative transcriptome profiling was performed using Illumina based RNA-seq to detect differentially expressed genes (DEGs) specifically modulated in response to Alternaria brassicicola infection in resistant Sinapis alba, a close relative of Brassicas, and the highly susceptible Brassica rapa. The analysis revealed that, at 48 hpi (hours post inoculation), 3396 genes were upregulated and 23239 were downregulated, whereas at 72 hpi, 4023 genes were upregulated and 21116 were downregulated. Furthermore, a large number of defence response or resistance associated genes have been detected to be specifically regulated as a result of Alternaria infection. The transcriptome data was validated using qPCR-based expression profiling for selected defense-related DEGs, that revealed significantly higher fold change in gene expression in S. alba when compared to B. rapa. Expression of most of the selected genes was elevated across all the time points under study with significantly higher expression towards the later time point of 72 hpi in the resistant germplasm. S. alba activates a stronger defense response reaction against the disease by deploying an array of genes and transcription factors involved in a wide range of biological processes such as pathogen recognition, signal transduction, cell wall modification, antioxidation, transcription regulation, etc. The study provides new insights on the resistance mechanism of S. alba against Alternaria infection which will aid in devising strategies for breeding resistant varieties of oilseed Brassica.